Factors that influence patient empowerment in inpatient chronic care: Early implementation experience with a diabetes care intervention in South Africa - Abrahams, Nina (Department of Public Health and Family Medicine, 2019)
The burden of non-communicable diseases is growing rapidly globally and especially in low and middle-income countries. However, health systems around the world are not appropriately prepared for this increase in need for chronic care. Research suggests that health models that emphasise self-management and empowering patients to care actively for their disease are integral in non-communicable disease treatment as patients live with their disease well beyond contact with health services. Adherence and health-seeking behaviour literature suggest multiple factors within the lives of patients and within health systems that enhance or constrain patient empowerment interventions. However, in depth understanding of these factors are lacking in the South African context and especially in the inpatient setting as most research focuses on the role of primary care. This research used interviews with stakeholders in an upcoming inpatient diabetes intervention as a lens to qualitatively explore empowerment factors in further detail within the South African inpatient context. The study highlights multiple barriers to patient empowerment, namely the low socio-economic contexts of many South Africans who then struggle to access appropriate healthcare information and services and often have financial and emotional priorities that take precedence over their chronic illness. In addition, health services are bound by a shortage of resources and staff and ineffective communication systems which affects health professionals’ ability to implement patient empowerment strategies. It also highlights the unique barriers found in inpatient care as the hospital emphasises short-term acute treatment – losing potential engagement time with patients. The study suggests that patient and provider contexts make encouraging patient engagement in long term chronic care difficult. However, knowledge of these factors can be harnessed to improve chronic care interventions in low- and middle-income countries.